(untitled) (Eurasian Journal of Ecology, 2016)
Three populations (9 of cenopopulations) a rare and relict species close endemic species Limonium michelsonii were investigated in the eastern part of the Trans-Ili Alatau (mountain Bogutty, hole Bartogay, mountains Toraigyr). Geobotanical descriptions of nine cenopopulations, the characteristics of soil and moisture were made as a result of the study. From 25 to 40 accounting areas were put in each population, the number of individuals of dominant and subdominant species were counted on them. Individuals of Limonium michelsonii by their age composition were pick out on each accounting areas, a full calculation of them with distribution by age categories was taken. Also, some measurements of biometric parameters of individuals of Limonium michelsonii were held on the accounting areas. Areal and area of distribution of this species have been found negligible in the study, also Limonium michelsonii prefers the loosened soil, areas with wind and water erosion. Age states of Limonium michelsonii most fully were represented in populations 2 and 3. There were the largest number of individuals of Limonium michelsonii on average on one accounting area in population 2 and the smallest number of individuals - in the population 3. Reproduction of Limonium michelsonii in three populations studied is the natural way - the seeds. Overgrazing is a great danger for the populations of Limonium michelsonii, because it does not tolerate trampling and grazing. The results, that were obtained in research, can be used to work out preservation measures of Limonium michelsonii, creating a database for the new release of the Red Book of Kazakhstan, etc.